THE INFLUENCE OF BRAND IMAGE AND CONSUMER TRUST ON THE DECISION TO PURCHASE THE ORIGINOTE SKINCARE PRODUCTS ON MANAGEMENT STUDENTS, FACULTY OF ECONOMICS AND BUSINESS, MUHAMMADIYAH MAKASSAR UNIVERSITY - Aisyah Nur Afni A; Aulia , Aulia; Andi Nur Achsanuddin (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study is to determine the influence of brand image and consumer trust on the purchase decision of the origionte skincare products in students majoring in Management, Faculty of Economics and Business, University of Muhammadiah Makassar. The type of data used in this study is quantitative data obtained from questionnaires that are shared and relate to the problem under study. Data collection was carried out by observation and distribution of questionnaires and processed through the Statistical Package for the Social Science (SPSS) version 29 application. The results of this study are brand image (X1) has a positive and significant effect on purchasing decisions (Y) with a value of (4.005 >1.966) and a significant value of <.001 which is smaller than the standard value of 0.05. While consumer confidence (X2) has a positive and significant effect on purchasing decisions (Y) with a value of (4.756 >1.966) and a significant value of <.001 which is smaller than the standard value of 0.05.